(untitled) (Research, Society and Development, 2021)
The objective was to analyze the effectiveness of educational tools in the knowledge of school educators about the management of dental avulsions, seeking to establish a relationship with the main initial behaviors and investigate information that are passed on to this public. This is an integrative review, whose data collection was carried out from primary sources, through bibliographic surveys in the databases PubMed, Web of Science, SCOPUS, LILACS, BBO and SciELO, from October to November 2020. Among the 461 findings and after using filters, reading of titles and abstracts, 9 studies were included to compose the review. The results of the study revealed that the participation of school teachers in an emergency situation is essential to provide good care to children, because the quality of these first aid will directly affect the long-term prognosis of avulsed teeth. For this, educational instruction methods were applied, such as: seminars, lectures, posters, dissemination of application and later application of a questionnaire to assess whether the knowledge of school educators has increased. After the instruction given by professionals or dental students, there was an improvement in the level of knowledge about the means of transportation of the tooth, with milk being cited in more than 50% of the studies and as for cleaning methods, the educators chose to wash the tooth with water or saline solution. It is concluded, therefore, that health tools and interventionist education programs have increased educators’ knowledge about the management of tooth avulsions.